Visitor Profiles at World Cultural Heritage Sites: An Empirical Study of Évora, Portugal - Borges, Maria do Rosário (2014)
Some of the most important historic cities are faced with a complex relationship between heritage conservation and tourism development. These sites are of unquestionable importance in strengthening a country’s tourism destinations. Every world heritage place, as recognised by The United Nations Educational, Scientific and Cultural Organization (UNESCO) has outstanding universal value. Some studies confirm that visits to these sites are almost justified by this prestigious classification and that motivations are closely associated with their cultural aspects and quality of the overall environment. The main purpose of the study is to define the tourist profile of the world heritage city of Évora and to determine the main motivations for visits to the destination. Based on visitor characteristics, the market segmentation was made. The methodology used is based on explanatory research to assess who the visitors are and why they choose Évora heritage site for their trips. The data collection technique applied was a visitor survey. The process adopted for the sample definition was a probabilistic sampling, namely the adoption of a stratified sampling plan, by place of residence. The central findings provide evidence that the fact that Évora is classified as a world heritage city is an important factor in destination choice. However, an analysis of the population means evidenced differences among the visitors (by place of residence) in the degree of influence of the fact that it is classified as World Heritage by UNESCO on the decision to visit Évora. For some markets this classification does not influence the decision to visit the city of Évora (USA, Netherlands and Portugal), but for others it greatly influences it (e.g. France, Japan and United Kingdom). The most important motivations for visitors in selecting Évora are leisure, heritage, gastronomy and wines and to have a new cultural experience.